Edge Computing in Mobile Networks: Enhancing Performance and Addressing Challenges - Anwer Hasan (Journal of Technology and System Information, 2025)
This research proposes a unified AI-based framework to enhance mobile network performance using edge computing. It introduces ARMA for latency reduction and CETO for energy optimization. Both algorithms rely on predictive analytics and adaptive task management. Implemented in Python and validated using NS-3 simulations and real telecom data, ARMA reduced latency by up to 50%, while CETO decreased energy use by 35%. Results were statistically significant (p < 0.05) across urban and rural scenarios. The framework provides a scalable, efficient, and secure solution for edge deployment, supporting real-time applications such as IoT and autonomous systems.